Improving The Methodology Of Developing Integrative-Creative Competences Of Students (Journal of Pedagogical Inventions and Practices, 2024)
This article is about the classification of educational problems, finding and analyzing their various solutions, and its complexity, which is considered an important characteristic of the educational problem, is a necessary parameter in finding ways to solve the problem. Classification of educational issues according to the level of complexity allows, on the one hand, to choose issues based on the set goals and real mental capabilities of learners, on the other hand, such an approach greatly helps students master the educational material